Measuring Civic Engagement in Young Children - McLoughlin, Shane; Polizzi, Gianfranco; Harrison, Tom; Moller, Francisco; Maile, Andrew; Picton, Irene; Clark, Christina (Journal of psychoeducational assessment, 2024)
There is a dearth of studies exploring how younger children engage in civic life, what may be expected of them given their age, and what instruments may be used to capture their levels of civic engagement. Addressing these questions, this article presents key findings from a pilot study that aimed to create a validated instrument designed to measure the civic engagement of primary school children. Based on a survey administered to 655 primary school children aged 9–11 across England, this article focuses on the new measure that was specifically designed, and then tested and validated through both exploratory and confirmatory analyses. The findings validate a tripartite measure of civic engagement that assesses the civic attitudes, actions and awareness of 9–11-year-olds. This measure was found to be both practical and efficient in its administration, and it has been shown to be easily comprehensible by this age group. This new measure addresses an important gap in the literature on civic engagement in children, providing researchers with a validated tool to effectively measure civic engagement in 9–11-year-olds. The findings have implications for both researchers and educators interested in designing and evaluating interventions aimed at promoting civic engagement among younger children.